Transforming Religious Learning with Macromedia Flash 8: Improving Students' Understanding of the Material on Faith in the Apostles - Melinda, Siska; Feizi , Farokh; Monfared , Parisa Naeimian (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine the effect of using Macromedia Flash 8 on student learning outcomes in the subject of Islamic Religious Education, material on Faith in the Apostles for Class XI at Aisyiyah 1 High School, Palembang. Methodology: This research employed a quantitative, quasi-experimental approach with two classes of 35 students each from XI Aisyiyah 1 High School, Palembang, divided into experimental and control groups. Instruments included written tests and Likert scale questionnaires, with Macromedia Flash 8 as the learning media. Data were analyzed using t-tests and descriptive analysis via SPSS to measure students' perceptions. Main Findings: The study found that Macromedia Flash 8 significantly improves student understanding of the concept of faith in the Apostles compared to conventional methods. The experimental group using Macromedia Flash 8 scored an average of 85.20, significantly higher than the control group’s 78.50 (p = 0.004). Additionally, students showed positive perceptions of this media, with 82.9% rating it as